Driving urban-rural migration through investment in water resource management in subsistence farming: the case of Machibini - Olayemi Bakre; Nirmala Dorasamy (Environmental Economics, 2017)
The once thriving subsistence farming community of Machibini is currently defunct due to water shortages, inadequacy of governmental support and better livelihood in urban communities. This community alongside its neighbouring communities is characterized by poverty. A variety of strategies and initiatives has been initiated to address the cyclical poverty amongst these communities. This paucity has driven the youths to urban centres as a means of securing a better livelihood. More so, the constant ebb of mass rural-urban migration has created voluminous challenges. As an agendum to creating a viable farming community in Machibini and “instigating an urban-rural migration”, the paper recommends the reallocation of the surplus budgets of this community to the investment of water resource management as a strategy of transforming the subsistence into commercial farming, thereby creating employment opportunities for the unemployed rural, as well as urban dwellers, while reducing poverty to a reasonable extent.